THE EFFECT OF SQ3R STRATEGY ON STUDENTS’ READING COMPREHENSION - Duvis Nava Yunensia Ovi Adila (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2018)
The objective of the study is to investigate the effectiveness of SQ3R strategy on students’ reading comprehension at State Junior High School 2 of Bululawang. The study used quantitative method with quasi-experimental design because there were two different groups for the samples namely experimental and control group and also the researcher gave different treatment for both experimental and control group. For experimental group the researcher taught by using SQ3R strategy while for control group the researcher taught by using skimming-scanning strategy. The researcher took VII A as control group and VIID as experimental group by using flipping coin. The instrument of this study was a reading test conducted twice as a pretest and post-test and the supporting instrument was a questionnaire. The results of hypothesis test showed that significance value was 0.000. So, there was a significance effect of SQ3R strategy on students’ reading comprehension at State Junior High School 2 of Bululawang. In other words, SQ3R strategy was effective and applicable for seventh grade students at State Junior High School 2 of Bululawang specifically on descriptivetext. Indeed, this strategy is recommended for teachers and students in learning English especially in reading skill to increase the students’ reading comprehension and stimulate the students’ activeness during teaching-learning process. Key Words: SQ3R Strategy, English Language Skill, Reading Comprehension.